Effect of Manuka honey, chlorhexidine gluconate and xylitol on the clinical levels of dental plaque - Prathibha A Nayak; Ullal A Nayak; R Mythili (Wolters Kluwer Medknow Publications, 2010)
Aims: To compare the effect of Manuka honey, chlorhexidine gluconate (0.2%) mouthwash and xylitol chewing gum on the dental plaque levels. Materials and Methods: Sixty healthy male dental students aged between 21 and 25 years (mean age 23.4 years) participated in the study. All the subjects received a professional prophylaxis at the start of the study, with the purpose of making the dentition 100% free of plaque and calculus. The subjects were then randomly divided into three groups, i.e. the Manuka honey group, the chlorhexidine gluconate mouthwash group and the xylitol chewing gum group. Rinsing with water or any other fluid after the procedure was not allowed as also any form of mechanical oral hygiene for all the subjects during the experimental period of 72 h. After the experimental period, the plaque was disclosed using disclosing solution and their scores were recorded at six sites per tooth using the Quigley and Hein plaque index modified by Turesky-Gilmore-Glickman. Results: The mean plaque scores for Groups I, II and III were 1.37, 1.35 and 1.57, respectively. The ANOVA revealed that between-group comparison was significant, with an F-value of 5.99 and a probability value of 0.004. The T-test was carried out to evaluate the inter-group significance, which revealed that the plaque inhibition by Manuka honey was similar to that of chlorhexidine mouthwash. Both Manuka honey and chlorhexidine mouthwash reduced plaque formation significantly, better than the xylitol chewing gum. Conclusion: Manuka honey and chlorhexidine mouthwash reduced plaque formation significantly better than xylitol chewing gum.